Kegiatan Berbagi Kasih: Pembagian Bubur Kacang Ijo Untuk Anak-Anak Yatim Piatu Sebagai Bentuk Kepedulian Sosial di Panti Asuhan Puteri Melati `Aisyiyah - Nurul Hidayat; Januari Darung; Kartini Kartini; Nirwana Nirwana; Syarima Z; Qoningatun Nashikhah (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
Sharing love is a form of caring for others, especially for orphans in orphanages. On Friday 20 September 2024, we held a love sharing event by distributing green bean porridge to orphans at the Puteri Melati `Aisyiyah Orphanage in Sebengkok, Tarakan. This event aims to provide simple happiness and strengthen ties between the community and children in orphanages. Social activities such as sharing food are often considered trivial. In fact, for those living in orphanages, healthy and nutritious food is an important need that is sometimes difficult to meet regularly. By distributing green bean porridge, we not only provide nutritional intake that is beneficial for the body, but also provide happiness and new enthusiasm for the children there. This activity is a form of love that they can feel directly, both through the taste of the food they enjoy and through our presence who provides attention and care. Apart from that, green bean porridge has its own meaning in the tradition of sharing in Indonesian society. As a food that is often associated with moments of togetherness and mutual cooperation, green bean porridge is a symbol of simplicity and sincere love. When this porridge is distributed in orphanages, it is not just food, but becomes a symbol of concern from those who care about the welfare of the children there. Social concern is an attitude of connection with humanity in general, an empathy for every member of the human community, for example female students. Community service is one of the media to hone student awareness in carrying out community service.